2022
DOI: 10.1038/s41598-022-18307-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring concerns about the COVID-19 vaccine among Japanese internet users through search queries

Abstract: With the increasing availability of the COVID-19 vaccines, vaccination has been rapidly promoted globally as a countermeasure against the spread of COVID-19. In Japan, vaccination was first introduced in February 2021. However, the amount of concern towards vaccination differs between individuals, and topics of concern include adverse reactions and side effects. This study investigated attitudes toward vaccines or vaccination during the COVID-19 pandemic across different Japanese prefectures, using Yahoo! JAPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Ferawati et al [ 32 ] explored how Twitter reported vaccine-related side effects by comparing the side effects of 2 types of messenger RNA vaccines developed by Pfizer and Moderna in Japan and Indonesia, respectively. Gao et al [ 33 ] examined COVID-19 concerns in each Japanese prefecture, and Uehara et al [ 34 ] investigated the attitudes toward vaccines or vaccination during the COVID-19 pandemic in different Japanese prefectures using search queries from Yahoo! JAPAN.…”
Section: Introductionmentioning
confidence: 99%
“…Ferawati et al [ 32 ] explored how Twitter reported vaccine-related side effects by comparing the side effects of 2 types of messenger RNA vaccines developed by Pfizer and Moderna in Japan and Indonesia, respectively. Gao et al [ 33 ] examined COVID-19 concerns in each Japanese prefecture, and Uehara et al [ 34 ] investigated the attitudes toward vaccines or vaccination during the COVID-19 pandemic in different Japanese prefectures using search queries from Yahoo! JAPAN.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy, safety, and immunogenicity of the COVID-19 and booster vaccines are established [5] , [6] , a substantial percentage of people worldwide have concerns [7] , hesitation [8] , and fear [9] . Moreover, concerns regarding adverse events may become barriers and decrease the COVID-19 vaccine/booster shot rate in young adults since the younger generation is more apprehensive and hesitant.…”
Section: Introductionmentioning
confidence: 99%
“…Although the e cacy, safety, and immunogenicity of the COVID-19 vaccines and booster vaccines are established [5,6] , a substantial percentage of people have concerns [7] , hesitation [8] , and fear [9] worldwide. As the younger generation is more concerned and hesitant, concerns about adverse events may become barriers and decrease the COVID-19 vaccine/booster shot rate in young adults.…”
Section: Introductionmentioning
confidence: 99%